Zinc: a potential star for regulating peritoneal fibrosis - Li, Jian; Li, Xinyang; Wang, Yangwei; Meng, Lingfei; Cui, Wenpeng (Frontiers in Pharmacology, 2024)
Peritoneal dialysis (PD) is a commonly used renal replacement therapy for patients with end-stage renal disease (ESRD). During PD, the peritoneum (PM), a semipermeable membrane, is exposed to nonbiocompatible PD solutions. Peritonitis can occur, leading to structural and functional PM disorders, resulting in peritoneal fibrosis and ultrafiltration failure, which are important reasons for patients with ESRD to discontinue PD. Increasing evidence suggests that oxidative stress (OS) plays a key role in the pathogenesis of peritoneal fibrosis. Furthermore, zinc deficiency is often present to a certain extent in patients undergoing PD. As an essential trace element, zinc is also an antioxidant, potentially playing an anti-OS role and slowing down peritoneal fibrosis progression. This study summarises and analyses recent research conducted by domestic and foreign scholars on the possible mechanisms through which zinc prevents peritoneal fibrosis.